Conservation of Food, Medicinal and Dye Plants Based on Local Wisdom of the Gumantar Village Community, Kayangan District, North Lombok Regency - Jupri, Ahmad; Isrowati, Isrowati; Wulandari, Astri; Sagita, Baiq Vira Emaliyana; Rahmatullah, Dimas Rizky; Ariani, Nurul Elda; Putri, Baiq Ega Zulqaidah; Madany, Lalu Riffadh; Uzma, Saadatul (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
Conservation of food, medicinal and dye plants is an important aspect in protecting biodiversity and ensuring the continuity of natural resources that are important for human life. This research is important because it combines the local wisdom of the people of Gumantar Village, Kayangan District, North Lombok Regency, in the conservation of food, medicinal and dye plants, which supports the sustainability of natural resources and local culture. This research aims to determine the types of medicinal, food and dye plants in Gumantar village and to find out how to use local plants as medicine, food and dye based on the local wisdom of the Gumantar village community. This research used a purposive sampling method, involving 10 people as representatives from each community in Gumantar Village. Data was collected through semi-structured interviews using a list of questions as a guide. In Gumantar village, various types of food crops are abundant, such as corn, rice, sweet potatoes, bananas, cocoa, sticky rice, coffee, peanuts, cashew nuts and coconut. Medicinal plants that are often used include turmeric, ginger, galangal, PKI leaves, cloves, citronella, lemongrass and lime. Natural coloring plants used include turmeric and suren bark.